Upaya Baznas Jepara dalam Menanamkan Kesalehan Sosial Pelajar melalui Program Pekan Peduli Sosial (PPS) - Murtadho Ridwan (Jurnal Bimas Islam, 2018)
The teachings of zakat, infaq and alms can form society that has the character to bear, ensure, and love each other. These qualities are the character of caring for others by giving. Charity Week (PPS) is Jepara BAZNAS program whose objects are students. The program aims to train students to care for others. This study aims to determine the implementation of the PPS program and to find out how the efforts of Jepara BAZNAS in instilling students' social charity through the PPS program. The approach used a qualitative approach with observation, interviews, and documentation as a data collection method. Data analysis used an analysis of the Miles and Huberman model. The results of the study show that the implementation of the PPS program began in 2011 and is carried out in the fourth week of August. Students in Jepara from PAUD, kindergarten, elementary / MI level at junior high school / MTs, senior high school / vocational high school / MA are asked to set aside pocket money for a week. Other results show that the Charity Week (PPS) program is an effort of BAZNAS Jepara in instilling student social charity because there is an element of giving and caring in PPS program which are two of the ten indicators of social charity. PPS acquisition has always increased in last three years shows that the spirit of students to give each other always grow. The reason to give is a sense to care for others and they realize that the money they set aside will benefit to the others. Ajaran zakat, infak dan sedekahdapatmembentuk masyarakatmemilikisifatsalingmenanggung,salingmenjamin,dan salingmengasihiantarsesama. Sifat-sifat tersebut merupakan sifat peduli terhadap sesama dengan cara memberi. Pekan Peduli Sosial (PPS) merupakan program BAZNAS Jepara yang objeknya adalah para pelajar. Program tersebut bertujuan melatih pelajar untuk peduli terhadap sesama. Kajian ini bertujuan untuk mengetahui pelaksanaan program PPS dan untuk mengetahui bagaimana upaya BAZNAS Jepara dalam menanamkan kesalehan sosial pelajar melalui progam PPS. Pendekatan yang digunakan adalah pendekatan kualitatif dengan observasi, wawancara, dan dokumentasi sebagai metode pengumpulan data. Analisis data yang dipakai adalah analisis model Miles and Huberman. Hasil kajian menunjukkan bahwa pelaksanaan program PPS dimulai pada tahun 2011 dan dilaksanakan setiap tahun di minggu keempat bulan Agustus. Para pelajar Jepara mulai dari tingkat PAUD, TK, SD/MI SMP/MTs, SMA/SMK/MA dan mahasiswa diminta untuk menyisihkan uang saku selama sepekan. Hasil lain menunjukkan bahwa program PPS menjadi upaya BAZNAS Jepara dalam menanamkan kesalehan sosial pelajar dikarenakan di dalam PPS terdapat unsur memberi (giving) dan peduli (caring) yang merupakan dua dari sepuluh indikator kesalehan sosial. Perolehan PPS yang selalu meningkatpada tiga tahun terakhir menunjukkan bahwa semangat suka memberi pelajar selalu tumbuh. Alasan mereka memberi adalah rasa peduli terhadap sesama dan mereka sadar bahwa uang yang mereka sisihkan akan bermanfaat bagi orang lain